Identifying groundwater resilience zones in an arid inland basin using GIS-based Dempster-Shafer theory - Yuehui Wang; Fengzhi Shi; Chengyi Zhao; Xu Zhou (Journal of Hydrology: Regional Studies, 2022)
Study region: Hotan River Basin, an arid inland river basin, Northwest China. Study focus: A method for assessing the spatial distribution of groundwater resilience is constructed by combining the Dempster-Shafer theory model and spatial analysis techniques. The groundwater performance indicator CRS and resilience indicator pi are calculated to present groundwater resilience. Using the Dempster-Shafer theory model to mine the data, nine groundwater conditioning factors are selected as evidential layers of the model, and the mathematical relationships between the resilience indicators and groundwater conditioning factors are established through evidence integration; Ultimately, a groundwater resilience spatial distribution map is generated, and the performance of the map is explored based on the CRS and pi values. New hydrological insights for the region: The constructed assessment method based on this study reliably and effectively predicts the regional groundwater resilience. Validation of the groundwater resilience prediction map with pi indicates that this indicator outperforms the CRS. The areas with high groundwater resilience are mainly concentrated in the upstream oasis irrigation area and the downstream river channel. The groundwater resilience (pi) zonation map is divided into five categories: very low (Bel of 0–0.072), low (0.072–0.171), moderate (0.171–0.458), moderate high (0.458–0.786), and high (>0.786). The results can provide a scientific basis for groundwater safety and management in the Hotan River Basin.